New evidence of predictive validity of SRSS-IE scores with middle and high school students - Lane, Kathleen Lynne; Oakes, Wendy Peia; Buckman, Mark Matthew; Lane, Nathan Allen; Lane, Katie Scarlett; Fleming, Kandace; Swinburne Romine, Rebecca E.; Sherod, Rebecca L.; Cantwell, Emily Dawn; Chang, Chi-Ning (Frontiers in Education, 2024)
We report predictive validity of the newly defined Student Risk Screening Scale – Internalizing and Externalizing (SRSS-IE 9, with 9 items) when used for the first time by middle and high school teachers from 43 schools. The sample included 11,773 middle school-aged students representing four geographic regions, and 7,244 high school-aged students representing three geographic regions. Results indicated fall SRSS-IE externalizing and internalizing latent factors as well as subscale scores (SRSS-E5, SRSS-I4, respectively) predicted year-end behavioral (office discipline referrals and in school suspensions) and academic (course failures) outcomes for middle and high school students as well as referrals to special education for middle school students. Internalizing scores also predicted referrals to special education for high school students. Externalizing and internalizing scores predicted nurse visits at the middle and high school levels with all models except for subscale models of internalizing in middle school. SRSS-IE 12 subscale scores for externalizing (SRSS-E7) and internalizing (SRSS-I5) using the original 12 items were similarly predictive of these outcomes, with few variations. We discuss educational implications, limitations, and directions for future inquiry.